Pengaruh Digital Payment Gateway, E-Commerce, dan Modal Dalam Meningkatkan Pendapatan Coffee Shop - Audina Amanda Putri; Andrian Noviardy (Benefit: Journal of Bussiness, Economics, and Finance, 2025)
This study aims to analyze both partially and simultaneously the influence of digital payment gateways, e-commerce, and capital on coffee shop revenue. The research employed a quantitative approach with a population consisting of MSME coffee shops in Palembang City. The sample was determined using purposive sampling, involving 30 respondents who had implemented at least one type of e-commerce platform and digital payment service. Data were collected using a Likert-scale questionnaire and analyzed through validity and reliability testing, classical assumption tests, and multiple linear regression. The findings indicate that digital payment gateways have a positive and significant effect on coffee shop revenue. Similarly, e-commerce significantly contributes to expanding market reach and increasing sales. Capital also shows a positive influence on the stability and growth of business income. Simultaneously, these three variables significantly affect revenue, underscoring the importance of integrating digital technology adoption and adequate capital in driving coffee shop income growth in the digital era.